Komunikasi Vaksinasi COVID-19 Nahdlatul Ulama dan Muhammadiyah di Twitter - Dimas Subekti (Jurnal Komunikasi, 2022)
Besides the government, many stakeholders also participated in spreading COVID-19 vaccination information in social media, including the two largest Islamic organizations, Nahdlatul Ulama and Muhammadiyah. This study was intended to describe the communications conducted by both organizations which were related to COVID-19 in the social media platform Twitter. The analysis was conducted using the NVIVO 12 method. This study discovered that Muhammadiyah utilized Twitter more frequently than Nahdlatul Ulama. The messages delivered by both Twitter accounts consisted of inconsistencies in COVID-19 policies, health protocols, COVID-19 collaboration vaccinations, and awareness towards the vaccinations.